2018
DOI: 10.1038/s41598-018-19876-z
|View full text |Cite
|
Sign up to set email alerts
|

Strong Fe3+-O(H)-Pt Interfacial Interaction Induced Excellent Stability of Pt/NiFe-LDH/rGO Electrocatalysts

Abstract: Agglomeration-triggered deactivation of supported platinum electrocatalysts markedly hinders their application in methanol oxidation reaction (MOR). In this study, graphene-supported nickel–iron layered double hydroxide (NiFe-LDH/rGO), in which Fe3+ was introduced to replace Ni2+ partially in the Ni(OH)2 lattice to provide stronger metal–support bonding sites, was utilized to immobilize Pt nanoparticles (NPs). Given the optimized metal–support interfacial contact (Fe3+-O(H)-Pt) between Pt NPs and NiFe-LDH/rGO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…High-magnification HAADF-STEM and TEM images indicated that uniformly dispersed ultrafine Pt NCs on the defect-rich NiFe LDH nanosheet surface with a narrow particle-size distribution (Figure 2c−f). Notably, TEM images showed that nanosheets treated with strong alkaline had a negligible change in the size distribution of Pt NCs except for the thinner nanosheets structure, 8,16 The highresolution TEM (HRTEM) illustrated that lattice fringes were coherently extended over the entire nanoparticle, confirming the formation of a single-crystal structure (Figure 2e), which was consistent with the selected area electron diffraction (SAED) pattern (inset of Figure 2c). The lattice spacing of 0.226 nm corresponded to the (111) planes of fcc Pt, 20 which was consistent with the XRD investigation.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…High-magnification HAADF-STEM and TEM images indicated that uniformly dispersed ultrafine Pt NCs on the defect-rich NiFe LDH nanosheet surface with a narrow particle-size distribution (Figure 2c−f). Notably, TEM images showed that nanosheets treated with strong alkaline had a negligible change in the size distribution of Pt NCs except for the thinner nanosheets structure, 8,16 The highresolution TEM (HRTEM) illustrated that lattice fringes were coherently extended over the entire nanoparticle, confirming the formation of a single-crystal structure (Figure 2e), which was consistent with the selected area electron diffraction (SAED) pattern (inset of Figure 2c). The lattice spacing of 0.226 nm corresponded to the (111) planes of fcc Pt, 20 which was consistent with the XRD investigation.…”
Section: Introductionsupporting
confidence: 73%
“…The adsorption energy of Pt NCs via the Fe 3+ − O(H)−Pt bonding was −4.87 eV, which was lower than that of Ni 2+ −O(H) −Pt bonding (−4.61 eV), suggesting the strong interaction of Pt NCs with site-specific Ni x Fe LDH sheets, which was consistent with previous studies. 16 Therefore, the Pt/Ni x Fe LDHs electrode displayed remarkable catalytic stability compared with that in the absence of the Fe precursor (Figure S16d). The observed slopes indicated that the ECSA was increased obviously after introducing a small amount of Fe elements while excessive usage led to negative effects (Figure S16e), which agreed well with the electrocatalytic performance.…”
Section: Introductionmentioning
confidence: 95%
“…A study by Liang and Liu provided additional guidance from the computational perspective on the bonding sites to immobilize noble metal atoms. 171 A model consisting of Pt and NiFe-LDHs, as shown in Fig. 13f, was constructed to elucidate the trend of the Pt The theoretical calculation revealed that Pt tended to bond with Fe 3+ ; therefore, the interaction between Fe 3+ and Pt was responsible for the site-specific loading and enhanced electrocatalytic activity of Pt-NiFe-LDHs.…”
Section: Decoration Of Noble Metal Atoms Into Ldh Nanosheetsmentioning
confidence: 99%
“…Copyright 2017, Elsevier Ltd. (f) Atomic structure of the Pt atom bonding to the ferric site in NiFe-LDHs. Reproduced with permission 171. Copyright 2018, the authors.…”
mentioning
confidence: 99%
“…Solid NiFe-LDH, possesses strong interplane chemical bonds but weaker out-of-plane van der Waals forces. 111 NiFe-LDH can be exfoliated and self-assembled with other layered materials like graphene, such as g-C 3 N 4 and MoS 2 , to form heterostructured materials. We have also reported different heterostructured materials of NiFe-LDH by the exfoliation strategy, composited with other layered materials such as in g-C 3 N 4 /NiFe-LDH, 27 Ag@Ag 3 PO 4 /g-C 3 N 4 / NiFe-LDH, 62 g-C 3 N 4 /N-rGO/NiFe-LDH, 33 and MoS 2 /NiFe-LDH.…”
Section: (B) Heteroassembly Of Nife-ldh/graphenementioning
confidence: 99%